Covid-19 Pandemic as a Catalyst for Digital Transformation: A Bibliometric Analysis using Vosviewer - Heri Purwanto; Lili Adi Wibowo; Agus Rahayu (Jurnal Manajemen Bisnis, 2023)
The pandemic of Covid-19 has become a global event that has an effect on every aspect of life. Since the announcement of Covid-19 as a pandemic on March 11, 2020 by the World Health Organization (WHO), until the end of December 2020 the pandemic is still ongoing in various parts of the world, a number of studies related to the impact of Covid-19 have been published in various international journals. This research aims to examine 446 articles related to Covid-19 as a catalyst for digital transformation in various fields that have received the researchers’ attention. By using a systematic literature review methodology and a bibliometric analysis approach, the results of the Vosviewer software analysis divide the emergence of keywords in both article titles and abstracts as many as 14 clusters which are divided into three subject areas of concern to researchers, namely psychology and health, socio-economics, and education. From those three fields, various digital technologies are utilized for digital transformation purposes, such as the internet of things, artificial intelligence, biosensors, digital health, e-learning, and others that can be used for further development for the benefit of more specific fields.